2019
DOI: 10.2147/ndt.s230348
|View full text |Cite
|
Sign up to set email alerts
|

<p>Methylenetetrahydrofolate Reductase Gene Variants Confer Potential Vulnerability to Autism Spectrum Disorder in a Saudi Community</p>

Abstract: Purpose: Several interacting genes or single nucleotide polymorphisms (SNPs) are vulnerable to the risk of autism spectrum disorder (ASD). Here we explored associations between SNPs in the methylenetetrahydrofolate reductase (MTHFR) gene or combined genotypes and the risk of ASD in a Saudi community. Subjects and methods: ASD severity symptoms were assessed according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) criteria and scores on the childhood autism rating scale (CARS). Genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…Consistent with this, a growing body of evidence suggests that the severity of autistic symptoms as a whole may be associated with increased levels of homocysteine associated with aggravation of dopamine deficiency (Carpita et al, 2023;Dangmann, 2023;Majhi et al, 2023). According to our data, rs1801133 of MTHFR, despite being less prevalent in our sample (12.9%) than in another cohort of Saudi children with ASD (36%) (Arab and Elhawary, 2019), was associated with a significant decrease in 9-OH-RIS and total active moiety levels, yet no evident impact was observed on RIS plasma exposure. The decreased concentration of the active moiety and a more pronounced effect on 9-OH-RIS could be explained by several factors.…”
Section: Mthfrsupporting
confidence: 87%
“…Consistent with this, a growing body of evidence suggests that the severity of autistic symptoms as a whole may be associated with increased levels of homocysteine associated with aggravation of dopamine deficiency (Carpita et al, 2023;Dangmann, 2023;Majhi et al, 2023). According to our data, rs1801133 of MTHFR, despite being less prevalent in our sample (12.9%) than in another cohort of Saudi children with ASD (36%) (Arab and Elhawary, 2019), was associated with a significant decrease in 9-OH-RIS and total active moiety levels, yet no evident impact was observed on RIS plasma exposure. The decreased concentration of the active moiety and a more pronounced effect on 9-OH-RIS could be explained by several factors.…”
Section: Mthfrsupporting
confidence: 87%
“…Previous studies have mainly focused on the influence of the MTHFR C677T on autism susceptibility, but the findings are still inconclusive. For example, (15) reported a correlation between MTHFR C677T polymorphism and a higher susceptibility to ASD, but this is not consistent with the findings of Dos Santos et al (16). A recent meta-analysis (17) suggested a significant association between them overall and by ethnicity, and thus the MTHFR C677T polymorphism could be used as a diagnostic marker of autism by ethnic background.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have investigated modifier genes and their relationship with behavioral features of the FXS phenotype (e.g., epilepsy, aggression, autistic features) [ 99 103 ]. One study found that the Val66Met polymorphism in the brain-derived neurotrophic factor ( BDNF ) gene may lessen the epilepsy phenotype in FXS patients, as this polymorphism can affect cerebral anatomy [ 104 ] and fragile X-associated neuropsychiatric disorders (FXAND) [ 99 107 ]. Evidence has been conflicting on whether variations in genes such as SLC6A4 (MIM 182138), MAOA (MIM 309850) , and COMT (MIM 116790) genes affect the severity of aggression, self-injury, and stereotypic behaviors in males with FXS [ 108 ].…”
Section: Molecular and Phenotypic Variabilitymentioning
confidence: 99%